Financial Performance of Nickel Companies Before and After the Nickel Ore Export Ban Regulation - Kristi Indriyani; Ewhidar Ewhidar; Shirley Wijaya (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
We used a few financial ratios in this study: the price-earning ratio (PER), net profit margin (NPM), debt-to-equity ratio (DER), current ratio (CR), and economic ratio (ER). Our goal is to gather actual data regarding changes in the financial performance of nickel companies listed on the BEI before and after the implementation of Permen No. 11 in 2019 regarding the export restrictions of nickel ore. This is a quantitative study that uses SPSS and the Paired T-test method. The financial accounts of nickel companies serve as a secondary data source for our investigation.